Antioxidant Activity of Antilisterial Bacteriocns Isolated from Paenibacillus polmyxa and Enterococcus faecium GRD AA - Krishna, Arya Radhakrishnan; Jayalekshmi, Swathy Krishna; Antony, Trisha Mary Pandipilly; Ramasamy, Suganthi (Asian Journal of Biological and Life Sciences)
Anti-listerial bacteriocin producing strain was isolated, purified and characterized from fermented food source toddy and milk and found to be the genus Paenibacillus polymyxa and Enterococcus faecium GRD AA. The bacteriocins ALC101 and ALC102 were partially purified by Amberlite XAD-16 purification method and anti-listerial activity were checked. Both the bacteriocins ALC101 and ALC102 along with Nisin showed a maximum of 85% of DPPH and 85.5% of ABTS radical scavenging activity like BHT which was the standard used in the assay. The bacteriocins also showed a maximum of 87.6% Fe2+ reduction potential. From the results it can be concluded as bacteriocin produced by Paenibacillus polymyxa ALC101, and bacteriocin from Enterococcus faecium GRD AA ALC102 has a good antioxidant potential when compared to Nisin and BHT (positive control).
Keywords: Antilisterial; Antioxidant; Bacteriocin; BHT; Nisin; Radical scavenging